Análise de expressões idiomáticas da língua portuguesa sob a perspectiva pedagógica - Cristiane Aparecida Soares da Silva Rozenfeld (2019)
Amid the typology of the units of the lexicon, we shall highlight phraseologisms that, in its turn, also have their own types. In this study, the object of analysis is the idiomatic expressions understood as syntagmatic lexical units, formed by two or more constituent elements, indecomposable, whose global meaning is different from the sum of the meanings of their component parts. In order to contribute to the development of lexical competence within Portuguese language classroom and in view of the cultural richness present in the lexicon of Brazilian Portuguese, we seek to address its idiomatic expressions from a pedagogical perspective. The aim of this work is to show the analysis of a set of idiomatic expressions collected from the lexicographic register of the main Brazilian school dictionaries. The methodology used, based on the theoretical support of Ferraz (2014), Corpas Pastor (1996), and Lewis (1993) started with a morphosyntactic description of idiomatic expressions. Afterwards, an analysis of the pragmatic effects of the various uses of such expressions takes place, involving aspects of synonymy and antonym, usage labels, conceptual fields, semantically transparent and opaque structures, all of which, according to Ferraz (2008), within a pedagogical approach. Thus, this study aims to answer the following questions: what are the relevant aspects of the study of idiomatic expressions, in Brazilian Portuguese, still absent? What approaches to idiomatic expressions could contribute to the development of lexical competence of high school students in Brazilian Portuguese language classroom? The corpus of analysis consisted of idiomatic expressions collected from the type 4 dictionaries, selected by PNLD-Dictionaries 2012. We organized the corpus collected in conceptual fields, in variant idioms, antonyms, synonyms, semantically transparent and non-transparent idioms, idioms formed with varied nouns and idioms that exist only in negative forms.